EVALUASI KEMAMPUAN LAHAN DESA SIHIONG, SINAR SABUNGAN DAN LUMBUN LOBU KABUPATEN TOBA SAMOSIR - Julpan Lynneus Sitohang; Sitorus Sitorus; Mariani Sembiring (Universitas Sumatera Utara, 2013)
Land capability evaluation is an evaluation of land potential for use of various farming systems in general without specifying the allocation to certain crops and management actions. The research was conducted in April of 2012. The purpose of this study was to determine the land capability class on Sihiong, Sinar Sabungan and Lumban Lobu Village Toba Samosir Distric with the method of limiting factors and matching according to land capability class Arsyad (1989). Analysis of the soil such as soil texture, permeability, bulk density, salinity and organic material are conducted in the Laboratory of Research and Technology, Faculty of Agriculture, University of North Sumatra and field observations such as slope, erosion factors, soil depth, drainage, gravel / rock and inundation / flood hazard. The results showed that areas Sihiong, Sinar Sabungan and Lumban Lobu has actual land capability class is the same class III (es), Class III is in which land can be used for the production of crops and forests, (es) an limiting factor on erosion and the depth of the root zone or soil (solum). So the capability class of potential land become III (s), which (s) is a limiting factor on the rooting area only. Keywords: evaluation of land capability, survey, BPS Tobasa